The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1371/journal.pone.0024087
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plant Species Richness Induce Functional Shifts in Soil Nematode Communities in Experimental Grassland

Abstract: BackgroundChanges in plant diversity may induce distinct changes in soil food web structure and accompanying soil feedbacks to plants. However, knowledge of the long-term consequences of plant community simplification for soil animal food webs and functioning is scarce. Nematodes, the most abundant and diverse soil Metazoa, represent the complexity of soil food webs as they comprise all major trophic groups and allow calculation of a number of functional indices.Methodology/Principal FindingsWe studied the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 48 publications
9
47
1
Order By: Relevance
“…Consistent with field experiments2632, soil microbial biomass increased with plant diversity, and soil microbial communities shifted along the plant diversity gradient towards more fungal-dominated communities633. While our results confirm previous experiments that reported plant biomass-mediated effects of plant diversity on soil microbial biomass32, the present study provides one of the first empirical evidences that this plant diversity effect could be driven –at least in part– by changes in plant root exudation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with field experiments2632, soil microbial biomass increased with plant diversity, and soil microbial communities shifted along the plant diversity gradient towards more fungal-dominated communities633. While our results confirm previous experiments that reported plant biomass-mediated effects of plant diversity on soil microbial biomass32, the present study provides one of the first empirical evidences that this plant diversity effect could be driven –at least in part– by changes in plant root exudation.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the measures of root exudate amount and diversity should be regarded as proxies representing relative differences among experimental treatments rather than absolute measures. Despite those caveats, the present study provides empirical evidence for the significant role of root exudates in linking above- and belowground communities and the diversity of plant communities with the functional composition of soil microbial communities1222 stimulating future work on the mechanisms of rhizosphere interactions262833.…”
Section: Discussionmentioning
confidence: 90%
“…In line with the results of Eisenhauer et al (2011), overall nematode density increased significantly with increasing plant diversity (after the flood), but that coincided with significant changes in nematode community composition.…”
Section: Increased Colonizer and Decreased Persister Nematode Densitysupporting
confidence: 86%
“…Through the SDS-PAGE analysis of protein standard achieved the standard curve (Fig. 5), the cellulase was figure out by measuring the relative mobility 10 and the cellulase molecular weight were 42.4 k D and 20.4 k D .…”
Section: Discussionmentioning
confidence: 99%
“…9 As a main soil animal, Nematodes are widely distributed in various habitats as the function soil animal species, which play an important role in soil ecosystem. 10 The response of soil microbes to nematodes is mainly reflected in the changes of biomass, microbial activity and microbial community structure. 11 The researchers found that nematodes could change the genetic structure of microbial communities with denaturing gradient gel electrophoresis (DGGE) through investigating 4 kinds of bacterivorous nematodes using microbial community culture system.…”
Section: Introductionmentioning
confidence: 99%